A noble metal-free proton-exchange membrane fuel cell based on bio-inspired molecular catalysts1. Issue 3 (16th March 2015) - Tran, P. D.; Morozan, A.; Archambault, S.; Heidkamp, J.; Chenevier, P.; Dau, H.; Fontecave, M.; Martinent, A.; Jousselme, B.; Artero, V.
<x xml:space="preserve">Abstract</x> Bio-inspired chemistry allowed for the development of the first noble metal-free polymer electrolyte membrane hydrogen fuel cell (PEMFC). The device proved operational under technologically relevant conditions.